Simple Acts to Save Our Planet: 500 Ways to Make a Difference - Michelle Neff (Simple acts, 2018)
Simple Acts to Save Our Planet shows you how to be more active in saving our planet every day by performing some "Simple Acts of Kindness"-for the Earth. Treat the environment with kindness with these easy, manageable activities that range from simple home updates, to gardening basics, to supporting the local community. You'll learn simple techniques to help protect the planet every day, like starting a compost pile to reduce food waste, utilizing travel mugs and reusable containers, and choosing eco-friendly products. By working to implement these simple strategies into your everyday life, you can take an active stand to protect the environment now- and make a real difference for the future.